Regulating Ai-Generated Content: A Comparative Study of Digital Rights And Algorithmic Accountability In Indonesia - Dikrurahman, Diky; Abdullah, Abdullah (Advances In Social Humanities Research, 2025)
The rapid proliferation of AI-generated content poses unprecedented governance challenges globally. In Indonesia, 212 million internet users face risks from deepfakes, misinformation, and algorithmic bias, while policymakers struggle to balance innovation encouragement against digital rights protection and algorithmic accountability. This research examines Indonesia's emerging regulatory approaches to AI-generated content, analyzing how proposed and implemented policies balance freedom of expression, innovation, and harm prevention. The study employs a qualitative exploratory case study design conducted over eight weeks, utilizing semi-structured interviews with 5-8 expert stakeholders (government officials, platform representatives, civil society advocates, legal scholars) and systematic document analysis of existing laws, proposed legislation, and comparative regulatory frameworks from the EU, Singapore, and US. Key findings reveal four critical insights. First, Indonesia's regulatory landscape remains fragmented, applying multiple pre-AI laws that inadequately address generative AI challenges, creating fundamental tensions between innovation and rights protection. Second, critical accountability gaps persist throughout the AI content lifecycle due to technical opacity, distributed responsibility, and limited redress mechanisms. Third, severe implementation constraints include technical capacity deficits, inter-agency coordination failures, enforcement difficulties against foreign actors, and political economy dynamics enabling corporate influence while marginalizing vulnerable populations. Fourth, Indonesia occupies a middle ground between the EU's comprehensive regulation and US market minimalism, adapting pragmatic approaches to its distinctive context. The study concludes that effective AI governance in developing countries requires five essential elements: substantial technical capacity investment, robust coordination mechanisms, accessible accountability systems, inclusive policy development processes, and international cooperation enabling meaningful regulatory authority rather than passive acceptance of externally-designed frameworks.